PERAN ORANG TUA DALAM MENDAMPINGI ANAK USIA DINI YANG MENGALAMI KECEMASAN SOSIAL: STUDI KASUS DI RA IHYAUSSALAFIYAH KETAWANG - Siti Nur Halimah; Nurhayati (LPPM IAD Probolinggo, 2025)
This study aims to analyze the role of parents in supporting early childhood children experiencing social anxiety at RA Ihyaussalafiyah Ketawang. Children aged 0–6 years are in a golden age that determines cognitive, socio-emotional, physical, language, creativity, and religious development. Social anxiety can hinder interaction, reduce self-confidence, and affect children's psychological development. The study used a qualitative approach with a case study design through in-depth interviews with parents, teachers, the principal, and observations of children's behavior at home and school. The analysis was conducted to find patterns, themes, and meanings regarding the role of parents in helping children deal with social anxiety. The results showed that attention, warm parenting patterns, and harmonious communication between parents and teachers are protective factors in fostering a sense of security, self-confidence, and children's social skills. The educational program at RA Ihyaussalafiyah encompasses cognitive, social-emotional, physical, creative, cultural, and Islamic values aspects and has been proven effective in supporting children's growth and development, while synergy between family and school creates a conducive learning environment enabling children to develop into intelligent individuals with Islamic character, caring for culture, and ready to contribute positively to society. Keywords: Early childhood; anxiety; parental involvement; parental role